Patient participation in medical consultations: the experience of patients from various ethnolinguistic backgrounds - Rhéa Rocque; Annabel Levesque; Yvan Leanza (The Beryl Institute, 2019)
Patient participation in health care is a priority. Yet, patients' perspective with regards to their experiences of participation is not well understood. Moreover, few studies have attempted to explore the perspective of ethnolinguistic minority patients. The objectives of this study, to explore 1) patients' experiences of participation in medical consultations with physicians, and 2) potential variations in these experiences based on participants' ethnolinguistic status. Using a qualitative design, 60 participants, from various ethnolinguistic background, took part in individual semi-structured interviews. A content analysis was performed to identify emerging themes. The results, five themes emerged in response to the first objective and are organized in two key dimensions: a) participation in terms of information exchange (e.g. asking questions, providing information), and b) participation in terms of assertive behaviours (e.g. setting the agenda, expressing one's viewpoint, making a request). Across these themes, two levels of participation emerged: proactive participation (i.e. patient initiated) and responsive participation (i.e. physician initiated). Proactive participation was discussed more often. Patients also discussed experiences of non-participation, although these were less common. In response to the second objective, patients who faced a language barrier, regardless of their ethnic background, discussed less participative experiences. In general, participants spoke positively of experiences in which they participated, thus suggesting that patient participation is valued by patients. Patients seemed to have a broad view of patient participation, thus suggesting that the concept of patient participation should be extended beyond participation in decision-making. Language fluency seems key to ensure patient participation.